Repeats influence structural DNA properties around functional annotations associated with 3D organization and transcription - Sievers, Aaron; Hausmann, Michael; Hildenbrand, Georg Lars (Genes, 2025)
Background: While the fundamental principles of chromatin 3D organization and its interplay with transcriptional regulation are still not completely understood, increasing evidence suggests a considerable role of DNA repeats. Considering the influence of DNA repeats on local dinucleotide contents, the influence of dinucleotide contents on the structural properties of DNA, their influence on histone affinity, and the influence of histone occupancy on chromatin, an indirect influence of repeats on 3D organization, seems worth testing. Methods: In this study, we search for global correlations between annotations associated with transcription and 3D organization, dinucleotide contents, DNA properties, and repeats in human and mouse. In a second step, we search for local peaks in DNA properties around those annotations and derive the influences of the dinucleotide and repeat contents (including tandem repeats (TRs) and transposons). Results: We identify several strong and significant associations between annotations and DNA properties, which are influenced by a variety of different repeats. Consistent with former findings, the Roll property is found to be especially sensitive to the sequence context. Conclusions: Our results suggest a significant effect of repeats on DNA properties and thus an indirect effect on histone occupancy and 3D chromatin organization.